Quanto vale uma pós-graduação stricto-sensu no Brasil?: os efeitos do mestrado e doutorado na remuneração de seus egressos - Lima, Diego de Faveri Pereira (2016)
This dissertation estimated the effects of a graduate degree on wages in Brazil with a database of 432.000 graduate degree holders and more than twelve million undergraduates that composed the control group. Significant effects were estimated ranging from 17.7% for the PhD to 13,0% for the Academic Master and 9,0% for the Professional Master. Sorting models were supported by the empirical results more than the predictions of human capital theory. Contrary to the expectations of both theoretical approaches, there was no effect of the quality of the courses on wages. The existence of a pure diploma effect, that would be associated to the regulation of higher education in Brazil was not confirmed by the empirical results.